2017
DOI: 10.1016/j.neuroscience.2017.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Cathodal transcranial direct current stimulation of the extrastriate visual cortex modulates implicit anti-fat bias in male, but not female, participants

Abstract: Explicit negative attitudes toward obese individuals are well documented and seem to modulate the activity of perceptual areas, such as the Extrastriate Body Area (EBA) in the lateral occipito-temporal cortex, which is critical for body-shape perception. Nevertheless, it is still unclear whether EBA serves a role in implicit weight-stereotypical bias, thus reflecting stereotypical trait attribution on the basis of perceptual cues. Here, we used an Implicit Association Test (IAT) to investigate whether applying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 87 publications
1
11
0
Order By: Relevance
“…The current findings expand this approach and show that the alpha rhythm during the IAT is significantly reduced after an intergroup dialogue intervention and this effect predicts long-lasting support of peacemaking. Consistent with our findings, Cazzato and colleagues used cathodal transcranial direct current stimulation of the occipital cortex to reduce the IAT effect ( 60 ) and similarly showed, using technology rather than dialogue intervention, that altering neural activity in occipital cortex is causally linked with reduction in intergroup bias. The findings from both studies highlight the potential of psychological and technological interventions to alter neural activity and consequently impact intergroup processes.…”
Section: Discussionsupporting
confidence: 88%
“…The current findings expand this approach and show that the alpha rhythm during the IAT is significantly reduced after an intergroup dialogue intervention and this effect predicts long-lasting support of peacemaking. Consistent with our findings, Cazzato and colleagues used cathodal transcranial direct current stimulation of the occipital cortex to reduce the IAT effect ( 60 ) and similarly showed, using technology rather than dialogue intervention, that altering neural activity in occipital cortex is causally linked with reduction in intergroup bias. The findings from both studies highlight the potential of psychological and technological interventions to alter neural activity and consequently impact intergroup processes.…”
Section: Discussionsupporting
confidence: 88%
“…Participants were required to answer as fast and accurately as possible after the onset of the stimuli (i.e., single words or images presented one at a time at the centre of the screen), by pressing a left (E) or a right (I) key on a computer keyboard with the index finger of the left hand and right hand, respectively. The IAT lasted approximately 8 min and was administered in seven blocks, consisting of both congruent and incongruent conditions (blocks 3, 4, 6, and 7) and familiarization blocks (blocks 1, 2, and 5) (Greenwald, Nosek, & Banaji, 2003; Cazzato, Makris, & Urgesi, 2017). Before the first presentation of the weight-IAT, participants were shown a list with all the words belonging to the two relevant categories and were asked to carefully read all the stimuli.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, we have shown that MR can be modulated by differences in the body weight between the actor and observer and that explicit negative attitudes toward overweight models can influence our ability to accurately simulate and predict the outcome of their actions (Cazzato & Makris, 2019). This is an interesting finding indicating that not only previous experience with an observed action, but also the existence of a negative stereotype (see also Cazzato, Makris, & Urgesi, 2017), can influence the level of one's ability to perceive others' actions and intentions. However, there is still limited evidence on how explicit and implicit anti-fat attitudes can influence the MR, as well as the underlying neural mechanism.…”
Section: Introductionmentioning
confidence: 83%
“…For the Weight-IAT, participants were required to answer as fast and accurately as possible after the onset of the stimuli (i.e., single words or images), by pressing a left (E) or a right (I) key on a computer keyboard with the index finger of the left hand and right hand, respectively. The IAT lasted approximately 8 minutes and was administered in seven blocks, consisting of both congruent and incongruent conditions (blocks 3, 4, 6, and 7) and familiarization blocks (blocks 1, 2, and 5) (Cazzato et al, 2017;Cazzato & Makris, 2019;Greenwald et al, 2003). Before the first presentation of the weight-IAT, participants were shown a list with all the words belonging to the two relevant categories and were asked to read carefully all of the stimuli.…”
Section: Weight-iat and Fat Phobia Scalementioning
confidence: 99%